FBN1 mutations largely contribute to sporadic non-syndromic aortic dissection. (18th September 2017) - Tan, Lun; Li, Zongze; Zhou, Chengming; Cao, Yanyan; Zhang, Lina; Li, Xianqing; Cianflone, Katherine; Wang, Yan; Wang, Dao Wen
Abstract: Mutations in FBN1 have been well identified in syndromic aortic dissection (AD) and familial thoracic aortic aneurysms and dissections. However, whether mutations of FBN1 contribute to sporadic non-syndromic AD and the characteristics of mutations remain unknown. Using next-generation-sequencing technology, FBN1 was sequenced in a total of 702 sporadic cases (including 687 of non-syndromic AD and 15 of sporadic Marfan syndrome with aortic event, and 527 normal controls). For the sporadic non-syndromic AD cohort, we found 26 variants in 27 patients (18 with missense, 2 frameshift, 1 initiation codon mutation, 3 nonsense and 3 splice site mutations). The prevalence of variants was significantly high in the sporadic non-syndromic AD cohort (27/687, 3.9%). The patients with FBN1 mutations were younger, suffered from fewer risk factors such as hypertension and smoking, and were less gender partitioned than non- FBN1 -mutation AD patients. The mutations were spread along the FBN1 gene in our sporadic non-syndromic AD cohort and mutation locations are not different between non-syndromic and syndromic patients. These results demonstrate that the deleterious mutations in FBN1 largely contribute to pathogenesis of sporadic non-syndromic AD, which expands our knowledge of FBN1 variants and the genetic basis and pathology of AD.